FROM YEKATERINODAR TO JEDDAH: ON THE PILGRIMAGE ROUTES OF THE ADYGHE OF THE KUBAN REGION IN THE EARLY TWENTIETH CENTURY - Neflaseva, Naima Aminovna (History, Archeology and Ethnography of the Caucasus, 2026)
This article addresses the previously unexamined issue of the pilgrimage routes taken by the Adyghe of the Kuban region to Mecca and Medina. The author aims to characterize the Hajj routes of Kuban’s Adyghe Muslims, including major railway and maritime waypoints, while identifying the local actors involved in organizing the pilgrimage. A pivotal role in organizing the Hajj for Muslims of the Russian Empire was played by the “Temporary Rules on Muslim Pilgrimage” of 1903. By the early 20th century, the authorities of the Kuban region had established a consistent practice for issuing the necessary documentation to prospective pilgrims. A central organizational figure for the Adyghe pilgrims was the philanthropist and entrepreneur L.N. Trakhov. He not only provided consultations regarding the upcoming journey but also assisted with ticket purchases, even funding the pilgrimage for some individuals at his own expense. The processing of documents took place in Yekaterinodar, where pilgrims submitted petitions for departure along with guarantees from their village elders (aul starshina) certifying their solvency and loyalty. The subsequent route proceeded by rail from Yekaterinodar to Novorossiysk. From Novorossiysk, the pilgrims traveled via Russian Steam Navigation and Trading Company (ROPIT) steamers to Sevastopol, and from there to Jeddah or Yanbu via Constantinople. In Sevastopol, the Hajilar Caravan Sarai was established on the coast to accommodate the pilgrims. Constantinople could be reached via the Sevastopol-Constantinople and Anatolian lines. For the transport of pilgrims, ROPIT allocated a specific Persian Gulf line, where conditions on board were adapted to meet the requirements of their ritual practices. In Constantinople, pilgrims registered at the Consulate General of the Russian Empire. The duration between receiving documents in Yekaterinodar and registering in Constantinople could range from seven days to one month.
Keywords: Hajj; pilgrimage routes; Russian Empire; Kuban region; Russian Steam Navigation and Trading Company (ROPIT); Adyghe; Muslims